Surgery in Peyronie's Disease: Our Experiences with Tunica Plication, Plaque Incision and Grafting with Gore-Tex, and Satisfaction Degree of the Patients - Giandomenico Passavanti; Anna Maria Aloisi (Archives of Renal Diseases and Management - Peertechz Publications, 2015)
Peyronie's  disease  is  a  relatively  common  condition,  with  an  incidence  of  3-9%.  It  is  often associated with diabetes and erectile dysfunction (ED). This condition causes a penile deformity that can  affect  sexual  penetration  and  lead  to  psychological  disorders  because  of  the  difficulty  in  coping with the situation. Sometime the surgery does not satisfy the patients; we tried to evaluate this aspect of the disease. Materials  and  methods: We  treated  46  patients  for  recurvatum  penis  secondary  to  Peyronie's disease.  The  clinical  examination  involved  an  accurate  medical  history,  a  physical  examination  to identify  the  plaque,  ultrasonography  to  detect  calcified  plaque,  and  a  photograph  of  the  erect  penis to document the recurvatum and sandglass deformity. In the case of ED, we administered the IIEF-5 and performed intracavernous injection of PGE1; in patients eligible for grafting, we also carried out a dynamic echo colour Doppler of the cavernous corps. Penis length, altogether, was between 11.5 and 14.5 cm (13.25 ± 1 cm). In 40 patients with moderate curvature (45-60°) we carried out tunica plication and in 6 cases with curvature >60° and with ED we performed plaque incision and partial dissection, with  grafting  strips  of  polyester  fluoropolymer  (Gore-Tex).  In  all  cases,  we  performed  an  extended dissection of the dorsal plexus and urethra.